The Factors Causing Work Fatigue among Nurses after COVID-19 Vaccination - Afandi, Alfid Tri; Kurniawan, Dicky Endrian; Nur, Kholid Rosyidi Muhammad; Ardiana, Anisah; Asmaningrum, Nurfika; Purwandari, Retno (Babali Publisher, 2024)
Introduction: Work fatigue is a risk for all workers, including nurses, who are constantly working to help meet patient needs. The effects of work fatigue when providing nursing care to patients can have an impact on reducing the quality of work so that it can impact patient satisfaction in receiving services. The aims of the study are to determine the factors that cause work fatigue in nurses after the COVID-19 vaccination program. Method: This research used an observational design with a descriptive-analytical approach. The location of this research is hospitals in Jember with a population of nurses who work in hospital inpatient rooms using a simple random sampling technique. The total number of respondents obtained was 165 nurses. The research instrument used in data collection was the Job Fatigue Feelings Questionnaire, which had been modified from KAUPK2 and consisted of 17 question items. Statistical analysis in this research uses a constant comparative method. Results: Based on the demographic data of respondents as an item from the analysis of nurses' work fatigue, it was found that age, education, and working period influence the level of work fatigue (p=0.01; p=0.04; p=0.04) while gender, marriage, employment, and position didn’t influence the work fatigue of nurses (p=0.82; p=0.93; p=0.14; p=0.48). Conclusion: Work fatigue can affect the performance of nurses. The most influencing factors were age, education, and working period, while marital status, employment, nursing position in work, and gender did not influence the level of work fatigue of nurses.